"A DEAF VARIETY OF THE HUMAN RACE": HISTORICAL MEMORY, ALEXANDER GRAHAM BELL, AND EUGENICS. (19th December 2014) - Greenwald, Brian H.; Van Cleve, John Vickrey
Abstract Alexander Graham Bell stood at the intersection of two late nineteenth-century American social developments. First, a nascent deaf community, threaded by residential schools and the use of a shared visual language, began to form by the 1850s, drawing deaf people into regular interaction and intermarriage. Second, the American eugenics movement, determined to eliminate perceived social problems through reproductive restrictions, came to prominence as the century neared its end. Bell's role in publicly connecting these two historical threads has earned him the approbation of the American deaf community and historians of disability. This article examines Bell's words and actions closely over thirty years to argue that a combination of Bell's own hubris and historians' tendency to conflate two aspects of his complex attitude toward disability has distorted historical memory. Bell feared that difference alone led to inequality, and he hoped that society could be improved through informed reproductive decisions. Ultimately, Bell found himself entangled in an alarming eugenic environment and sought to thwart eugenicists who would interfere with deaf reproductive rights.